A Review on the Microaggressions on the Internet: A Framework to a Discrimination-Free Cyberspace - Guerrero, Jeraldine; Catibag, Pol Jay; Casauay, Angeli Faye; Esteban, Felimon; Salazar, Flordeliza; Aquino, Jay Ar; Turqueza, Rosalie; Erece, Rizabelle; Ramos, Princess; Cabansag, Grace (International Journal of Arts, Sciences and Education, 2022)
This study aimed to review the justifications of online users on the frequently observed microaggressions on the internet in the time of COVID-19 and to find out whether these microaggressions are offensive or non-offensive. It was found out that the most frequently observed microaggressions on the internet are stereotypes, prejudice, oppression, and various forms of discrimination like racism, sexism, colorism, classism, and ageism. Through an online-based questionnaire, the researchers could get participants' justifications whether a situation containing microaggression was offensive or not. The researchers found out that most participants felt offended by most of the posts and tweets (researched to be microaggressive) presented by researchers because of the following reasons: (1) Name-calling someone because of their expression and traits and using it as an insult is offensive; (2) Messages convey rudeness and insensitivity; (3) Invalidation of racial reality such as experience, thoughts, and feelings. Also, some participants viewed some posts and tweets (researched to be microaggressive) presented by the researchers as non-offensive because of following reasons: (1) The post presented does not affect them; (2) The post does not show judgment to any person; (3) They do not care about the post at all; (4) They do not understand the meaning of the post; (5) Some of the posts are considered as jokes and endearment.